Enhancing potential of hydrofracturing in mylonitic coal by biocementation. Issue 4 (6th January 2021) - Song, Chenpeng; Zhi, Sheng; Feng, Gan; Lin, Junzhi
Abstract: Mylonite coal is a representative of tectonically deformed coal and is a result of crushing original coal into fine coal grains under strong shear or long‐low tectonic stress. Because of its granular nature and the resultant inferior mechanical property, it is difficult to initiate fluid‐driven fractures within mylonitic coal reservoirs for enhancing coalbed methane recovery. The following explores a biomineralization method of microbially mediated calcium carbonate precipitation (MICP) to enhance the structural integrity and mechanical strength of mylonitic coal, enabling potential success for hydrofracturing. The experimental results indicate that the mechanical properties of mylonite coal are significantly enhanced after a short period of MICP treatment with ten cycles of treatments yielding a maximum uniaxial compressive strength (UCS) of 8.7 MPa and a maximum brittleness index of 0.218 approaching that of the hard coal. The increments in UCS and brittleness of biocemented mylonite coal show a positive correlation with the generated calcium carbonate content. Scanning electron microscopy (SEM) imaging indicates that the generated calcium carbonate precipitates first randomly occur on the particle surfaces, and then occupies the interstitial space until particle‐particle bonds are developed. The irregular morphology of coal particles results in two contact relations between particles, point contact and planar contact, causing a significant difference in biocementation effectiveness. Two microfailure patterns of biocemented coal with uniaxial compression are observed. One is that the coal particles are crushed, and the other occurs at the biocemented interface between the coal particles and calcium carbonate crystals. Abstract : One potential method for enhancing the potential of hydraulic fracturing in mylonitic coal has been investigated. SEM results show calcium carbonate precipitation occurs first on the surface of coal particles, irregularly occupying the interstitial space, before creating particle‐particle bonds. The calcium carbonate content shows a positive correlation with the macroproperties of permeability reduction, strength, and brittleness for sample.